Improving compliance of risk assessment and nonpharmacological interventions for deep venous thrombosis prevention in a respiratory ICU: a best practice implementation project. Issue 3 (5th September 2021) - Wu, Jinyan; Zhu, Shunfang; Munn, Zachary; Zhou, Chunlan
ABSTRACT: Objectives: To increase the compliance with deep venous thrombosis (DVT) nonpharmacologic prophylaxis best practice recommendations while ensuring appropriate and structured nonpharmacologic prophylaxis for patients in the respiratory ICU. Background: DVT is a major problem for patients, with those who are critically ill representing a high-risk population for developing the condition. Nonpharmacologic prophylaxis is considered an effective intervention. However, the application of such interventions in practice has not been optimal to date. Methods: The current project was conducted in a respiratory ICU of a tertiary hospital. Audit criteria were developed on the basis of an evidence summary developed by the Joanna Briggs Institute, whereby the institute's Practical Application of Clinical Evidence System program to facilitate an audit and feedback cycle was utilized as an implementation framework. Baseline and follow-up audits on nonpharmacological DVT prophylaxis were conducted for 35 patients against five evidence-based recommendations. In addition, the nurses' knowledge and attitude regarding DVT prophylaxis were investigated both prior to and postimplementation. Results: In the baseline audit, compliance with the five evidence-based audit criteria was less than 15%. After the implementation of strategies including education, person-centered care, financial and human-resource support, there was a significant improvement in all the audit criteria. In addition, improvements in the nurses' knowledge and attitude regarding DVT prophylaxis were reported. The rate of discharged patients due to a deterioration of their condition decreased from 31.4 to 5.7% in the follow-up cycle. One DVT patient occurred in the baseline data, whereas no new incidences of DVT were found in the follow-up data. Conclusion: The project not only improved nurses' knowledge and attitude regarding DVT prevention, but also remarkably improved the implementation of nonpharmacological DVT prophylaxis. The application of evidence-based nonpharmacological DVT prophylaxis may improve patients' outcomes in the ICU.